Access to healthcare insurance increases the rates of surgery for diverticulitis. (2nd October 2021) - Eguia, Emanuel; Classen, Timothy; Choudhry, Mashkoor; Singer, Marc; Eberhardt, Joshua
ABSTRACT: Objective: The goal of this study was to examine the effect of the Affordable Care Act Medicaid expansion on rates of hospitalization and surgery for diverticulitis. Study Settings: Data were obtained from the Healthcare Cost and Utilization Project State Inpatient Databases from 2010 to 2014. Study Design: Retrospective cohort study analyzing adult patients undergoing surgery for diverticulitis in the expansion and nonexpansion states, pre (2010-2013) and post (2014) Medicaid expansion. Findings: There were a total of 159, 419 patients in our cohort analysis. 75, 575 (49%) in expansion states and 81, 844 (51%) in non-expansion states. In multivariable Poisson regression, the rate of surgical procedures for diverticular disease increased among Medicaid patients (IRR 1.80; p < .01) whereas surgery rates in self-pay patients decreased (IRR 0.67; p < .01) in expansion states compared to non-expansion states. Conclusions: In states that expanded Medicaid coverage under the Affordable Care Act, the rate of surgery for diverticular disease in Medicaid patients increased. Therefore, legislation that increases healthcare access may increase the utilization of surgical care for diverticular disease.